Energia de interação cátion-ânion de líquidos iônicos dicatiônicos em fase gasosa - Hennemann, Bruno Luís (2016)
Electrospray ionization mass spectrometry (ESI-MS) with induced collision energy was used to carry out a comprehensive study on the interaction energies between cations and anions of dicationic ionic liquids. The influence of the anion ([Br]-, [NO3]-, [BF4]-, [SCN]- and [Cl]-) and the size of alkyl chain (n = 4,6,8 and 10) in the interaction energy of ionic liquids derived from the 1, n-bis (3-methylimidazolyl-1-yl) alkane with n = 4,6,8 and 10, in the gas phase was investigated. Three experiments were carried out to determine the cation-anion interaction energy: (i) ESI-MS of binary (1:1) mixtures of ionic liquids with different anions or cations; (Ii) ESI-MS of ionic liquid individually with variation of the applied collision energy and determination of the center of mass energy (Ecm) using the relation between the intensity of the precursor ion and the sum of the ions; (iii) the rate of variation of the intensity of the precursor ion as a function of collision energy at different concentrations of all ionic liquids was obtained. From this correlation, the cation-anion dissociation constant of the dicationic ionic liquids was obtained. The results showed the appearance of mixed species (example: [Bis-C8(MIM)22XY]- and [C8(MIM)XY]-) in the binary mixtures. The application of the induced collision energy in the mixtures allowed estimating which anion interacts more effectively with the cation. Also for this experiments, the dicationic ionic liquids with the anions [Cl]-, [Br]- and [NO3]- presented higher cation-anion interaction energy. The increasing order of interaction energy was [BF4]- <[SCN]- <[NO3]- <[Br]- <[Cl]-. The Ecm values for ionic liquids with different anions did not indicate trends in the interaction energy in relation to structural factors such as ionic radius and molecular volume. Thus, for the anions, it was found that the interaction increases in the following order: [SCN]- <[Cl]- <[NO3]- <[Br]- <[BF4]-. On the other hand, increasing the size of the spacer alkyl chain caused an increase in cation-anion interaction energy. As the concentration of the ionic liquid increased, an increase in the precursor ion intensity was observed.